LC-ESI-QTOF-MS/MS characterization of phenolic compounds from Prosopis farcta (Banks & Sol.) J.F.Macbr. and their potential antioxidant activities - Sharifi-Rad, Javad; Zhong, Jianshu; Ayatollahi, Seyed Abdulmajid; Kobarfard, Farzad; Faizi, Mehrdad; Khosravi-Dehaghi, Nafiseh; Suleria, Hafiz A.R. (Cellular and Molecular Biology, 2021)
Prosopis farcta (Banks & Sol.) J.F.Macbr. is an emerging medicinal plant containing a diverse array of phytochemicals, including protein, fat, carbohydrate, fibre, alkaloids, fatty acids, glycosides, and polyphenols, with strong antioxidant potential. However, the screening and characterization of phenolic compounds in P. farcta is limited. This study is conducted to determine the polyphenol contents and their antioxidant activity in P. farcta leaves samples via liquid chromatography-electrospray ionization quadrupole time-of-flight mass spectrometry (LC-ESI-QTOF-MS/MS) and high-performance liquid chromatography-photodiode array (HPLC-PDA). Total phenolic content (TPC), total flavonoid content (TFC), and total tannins content (TTC) were determined for polyphenol estimation. The antioxidant properties were measured by total antioxidant capacity (TAC), 2,2'-Diphenyl-2-picrylhydrazyl (DPPH), Ferric Reducing Antioxidant Power (FRAP), and 2,2"²-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS). LC-ESI-QTOF-MS/MS was used to identify and characterize 47 phenolic compounds, which mainly included phenolic acids (13), flavonoids (28), other polyphenols (4), lignans (1), and stilbenes (1). According to HPLC-PDA quantification, chlorogenic acid (9.78 ± 2.15 mg/g dw) was the most abundant phenolic acid, while the main flavonoids included catechin (12.73 ± 1.29 mg/g dw) and kaempferol (7.93 ± 1.47 mg/g dw). The study demonstrated the significance of P. farcta as a rich source of phenolic compounds with antioxidant capacity that can be widely used in food, beverage, feed, and pharmaceutical applications.